INGLIZ TILI GRAMMATIKASINI INDUKTIV VA DEDUKTIV USULLARDAN FOYDALANGAN XOLDA O`RGATISHNING BIR BIRIDAN FARQI - Dauletmuratova, M.Y. (SCIENCE and SOCIETY, 2023)
There are analyzed the differences of using inductive and deductive ways of teaching grammar and their peculiarities in this article.
Keywords: foreign languages; science; political; economic; social; cultural and scientific relations; the English language; inductive and deductive methods; schools; modern technologies; online channels